Billionaire Wealth, Firm Performance and Financial Crisis: An Empirical Analysis for India. (December 2016) - Ghosh, Saibal
Employing data for 2001–2012, the article analyzes the factors impacting the wealth of Indian billionaires and the performance and innovative activity of firms which these billionaires represent. The analysis indicates that billionaires in rent-thick sectors have higher wealth levels, on average. As well, the evidence also supports lower wealth for self-made and entrepreneurial billionaires. The findings also reveal that self-interested actions by billionaires tend to raise agency costs, which, in turn, dampens profitability and firm value. Finally, there is evidence which suggests a tendency on the part of billionaires to block innovative activity. JEL Classification: D31, N35, P52